Specialist Bee Species Are Larger and Less Phylogenetically Distinct Than Generalists in Tropical Plant–Bee Interaction Networks - Raiol, Rafael Lobo; Gastauer, Markus; Campbell, Alistair John; Borges, Rafael Cabral; Awade, Marcelo; Giannini, Tereza Cristina (Frontiers in Ecology and Evolution, 2021)
Bee pollinators are key components of terrestrial ecosystems. Evidence is mounting that bees are globally in decline, and species with a higher degree of specialization are the most vulnerable to local extinction. However, ecological features that could explain bee specialization remain poorly tested, especially in tropical species. Here, we aim to determine the most specialized bee species and their associated ecological traits in tropical bee-plant interaction networks, answering three questions: (1) Which bees in the interaction networks are specialists? (2) Is body size related to their role as specialists in interaction networks? (3) Are there phylogenetic relationships between the bee species identified as specialists? We used fifteen quantitative plant-bee interaction networks from different Brazilian biomes covering 1,702 interactions (386 bee and 717 plant species). We used the normalized degree (standardized number of partners) as a metric to determine trophic specialization of bee species. Body size was estimated by measuring intertegular distance (ITD), i.e. the distance between the bases of the wings on the thorax. Evolutionary distinctiveness (ED) was used to quantify species uniqueness, i.e. the singularity of species’ genomes and functions within the clade. Relationships between dietary specialism, ITD and ED were assessed using generalized linear models. We detected 34 specialist bee species (9% of total species), distributed in 13 genera, and four families. ITD and ED were important variables explaining the specialization of tropical bee species. Specialists were larger and less phylogenetically distinct than expected by chance. Based on a large data set covering some of the main tropical biomes, our results suggest that loss of specialist bees from Brazilian bee-plant networks could have deleterious consequences for native plant species exclusively pollinated by large-bodied bees. Moreover, by affecting more evolutionarily distinct species, i.e. those with fewer extant relatives, the loss of specialist bees will likely affect few clades but can result on considerable loss of evolutionary history and phylogenetic diversity in the Brazilian bee communities. The results are important for decision-making concerning conservation measures for these species and may also encourage the development of sustainable management techniques for bees.